Market Analysis of Shipping MBA Programs - Kärpijoki, Essi (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
This study concentrates on getting a better understanding of Shipping MBA (Master of Business Administration) programs. MBA is an international degree aimed for graduates and professionals to develop their business and management skills. Shipping MBA is a degree specialized for shipping industry professionals’ education needs. The purpose of this study is threefold: First to conduct a market analysis of available Shipping MBA programs. This is done by defining the Shipping MBA market, target market and market segments. Second aim is to study the curriculum of these Shipping MBA programs. This is based on literature and course material review. Documentary evidence about each Shipping MBA program is the core empirical material of the study. And third this study strives to estimate the need and market potential for Shipping MBA education currently and in the near future. This is done by assessing current supply and demand of Shipping MBA programs and based on that also future demand is evaluated. Finally, competitive forces in Shipping MBA market are discussed in context of Porter’s five forces model. This study led to a notion that the Shipping MBA education is quite heterogeneous a group with different characteristics. The degree of specialization, studying method, price of the degree and geographical coverage are varying from program to program. However, certain core courses were included in almost every Shipping MBA program, such as courses on: introduction to shipping business, maritime law, strategy, business management and business finance. It was noted that Shipping MBA programs have future market potential but the current market demand is quite modest. It can be assumed that currently Shipping MBA business is not very profitable for the program suppliers.